Framework to elicit multidimensional requirements - Serna M., Edgar (Pontificia Universidad Javeriana, 2018)
Objective: Propose a framework to elicit multidimensional requirements. Materials and methods: A review of the literature is carried out, and the elicitation proposals are analyzed in which the multidimensionality of the requirements is taken into account. Results and discussion: 23 works were found, of which 15 were selected that met the quality conditions and inclusion criteria. These proposals are related to multidimensionality in elicitation but do not take it into account in order to construct a representative requirement specification. Conclusion: It is evident that there is no unanimity about the dimensions from which the requirements originate, and they have not been elicited. For this reason, and because its existence is accepted, it is necessary to unify criteria and propose frameworks to elicit multidimensional requirements.